Pattern of congenital heart diseases among clinically diagnosed Downs syndrome children (Northern International Medical College Journal, 2015)
Background : Downs syndrome (DS) is the commonest genetic cause of malformation with congenital heart defects.Objectives : This study was conducted to evaluate the frequency of various congenital heart defects in children with clinically diagnosed Downs syndrome in Dhaka Shishu Hospital.Material & Methods : This prospective study was conducted at Pediatric cardiology department of Dhaka Shishu Hospital from 1st February 2013 to 31st January 2014. Admitted Seventy four phenotypically Downs syndrome patients were included in this study. After taking detailed history and physical examination, all these patients were subjected to Color Doppler echocardiography in addition to routine laboratory investigations.Results : Total 74 downs Syndrome patients were admitted at cardiology department during the study period. Among them 35 (47.29%) were males and 39 (52.71%)were females with male to female ratio of 1:1.12. Atrioventricular septal defect was the commonest defect 15(20.27%), followed by Ventricular septal defect 12(16.21%), Patent ductus arteriosus 11(14.86%), Atrial septal defect 7(9.46%), Tetralogy of Fallots 3(4.05%), Pentology of Fallots 2(2.70%), Dextrocardia with D _ TGA 1(1.35%), Total anomalous pulmonary venous drainage 1(1.35%) but Multiple congenital heart disease were 22(29.72%) cases. Along with congenital heart disease 3(4.05%) patients had GIT abnormality, 4(5.4%) patient had congenital hypothyroidism and 3(4.05%) patients had Eye problem.Conclusion : Congenital heart defects are common in children with Downs syndrome. The commonest one is Atrioventricular septal defect in our set-up.Northern International Medical College Journal Vol.6(1) 2014: 18-20